Elaboración de un video documental para dar a conocer la explotación a través del trabajo infantil en la plazoleta el salto del cantón Latacunga durante el año 2015-2016 - Moreno Amores, Luis Gabriel (2016)
At present the lack of audiovisual information on child labor is scarce so it has been necessary include an audiovisual resource aware people; therefore this research project is to develop a video documentary on child labor exploitation in the small square Salto del Latacunga Canton during the year 2015 2016. Within the audiovisual field this video documentary will be purely social diffusion material which will be used for purpose of helping the community nonprofit, generating a job that supports learning in the Carrera Computerized Graphic Design.